(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
In 1938 the competition for the Imperial Square E42 signs the end the Scuola Romanaâ€™s â€œOther Modernismâ€ â€“ an experimental period most sensitive to the values of the organic city. The design of the square, although eventually distorted by many compromises, became a cornerstone in the architectural research of Ludovico Quaroni. After the War, in spite of the ideological barrage of his opponents (particularly those within the School of Architecture) Quaroni continued his enquiry which eventually led him, forty years later, to conceive the extraordinary design of the Opera House in Rome.